The Role of Vocational Accountants To Support SDG's Through Green Accounting - Armadhana, Annisa Nur Maghfirah; Wati, Ririn Reyna; Rahmatullah, Sri Wahyu; Wijayani, Dahyang Ika Leni (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
This study intends to determine the role of accountants in supporting Sustainable Development Goals (SDGs) and to what extent vocational education prepares accounting graduates in establishing green accounting as an effort to support the achievement of SDGs. The research method employed is qualitative descriptive, employing literature review and content analysis. The research findings conclude that accounting education plays a crucial role in achieving SDGs, particularly in vocational education. However, out of the 19 polytechnics in Indonesia that provide business/accounting programs, only 2 of them have courses specifically related to green accounting. This indicates both challenges and opportunities for vocational colleges in preparing their graduates to have skills related to sustainable accounting or green accounting. One of the efforts that can be undertaken is implementing an update to the curriculum with a focus on sustainability accounting and ensuring that accounting graduates have competencies related to green accounting.